2020
DOI: 10.1101/2020.02.10.940734
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecotype Simulation 2: An improved algorithm for efficiently demarcating microbial species from large sequence datasets

Abstract: BackgroundMicrobial systematists have used molecular cutoffs to classify the vast diversity present within a natural microbial community without invoking ecological theory. The use of ecological theory is needed to identify whether or not demarcated groups are the ecologically distinct, fundamental units (ecotypes), necessary for understanding the system. Ecotype Simulation, a Monte-Carlo approach to modeling the evolutionary dynamics of a microbial population based on the Stable Ecotype Model of microbial spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…This allowed us to restrict most analyses to sequences that were frequently detected. Also, analyses of HFS10s have proven valuable by increasing the sampling of variants within putative ecotypes, thereby enhancing our ability to demonstrate that sequence diversity within a putative ecotype is ecologically homogeneous (Becraft et al, 2015;Wood et al, 2020). However, we still used all sequences with >1 representative to analyze dispersal (see below).…”
Section: Molecular and Phylogenetic Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…This allowed us to restrict most analyses to sequences that were frequently detected. Also, analyses of HFS10s have proven valuable by increasing the sampling of variants within putative ecotypes, thereby enhancing our ability to demonstrate that sequence diversity within a putative ecotype is ecologically homogeneous (Becraft et al, 2015;Wood et al, 2020). However, we still used all sequences with >1 representative to analyze dispersal (see below).…”
Section: Molecular and Phylogenetic Analysismentioning
confidence: 99%
“…To analyze the distribution of HFS10 variation within ecological populations among chemically similar springs and regions, Ecotype Simulation 2 (ES2) was used to predict putative ecotypes (PEs) from the variation sampled. ES2 uses evolutionary simulation analysis to predict ecologically distinct or geographically isolated clusters in a phylogeny (Wood et al, 2020). Directions for download and instructions for the use of ES2 are freely available at https://github.com/sandain/ecosim.…”
Section: Putative Ecotype Demarcationmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, sequence clusters identified by Ecotype Simulation have all been shown to be ecologically distinct from one another (Connor et al, 2010;Ward et al, 2005;Koeppel et al, 2008). The Ecotype Simulation 2 (ES2) algorithm was used to demarcate putative ecotypes in the foundational study for this thesis (DelGaudio, 2018;Wood et al, 2018).…”
Section: Ecological Approach To Bacterial Systematics: Ecotype Theorymentioning
confidence: 99%